Antibacterial activity of aqueous and lipid extracts of five common allergenic pollens - Zahra Bashiri; Masoud Yousefi; Simon G Royce; Mohammad Fereidouni (Institue of Medicinal Plants, ACECR, 2022)
Background: Different parts of plants are rich sources of bioactive ingredients and have received much attention during recent decades. Objective: The aim of this study was to assess the antibacterial properties of five common allergenic pollens extracts. Methods: The aqueous and lipid extracts were prepared from allergenic plant pollens including Amaranthus retroflexus, Chenopodium album, Artemisia vulgaris, Cupressus arizonica, and Ailanthus altissima. Antibacterial activity of the extracts was determined using the broth microdilution method against ATCC bacteria strains. Results: Total protein content of aqueous extracts was form 453 to 2772 μg/ml, but for all lipid extracts it was less than 0.2 μg/ml. Aqueous pollen extracts of C. album, C. arizonica and A. altissima (MIC between 38.8 to 562 μg/ml), and the lipid pollen extracts of C. album, C. arizonica, A. altissima, A. retroflexus, and A. vulgaris (MIC between 0.89 to 21.9 μg/ml) had a significant antibacterial activity on E. faecalis. Moreover, the aqueous pollen extract of A. altissima (MIC = 8.7 μg/ml), and the lipid pollen extracts of C. arizonica, A. altissima, A. retroflexus, and A. vulgaris (MIC between 1.78 to 21.9 μg/ml) showed a significant antibacterial activity against S. aureus. The only extract with antibacterial effect on K. pneumoniae was the lipid pollen extract of A. vulgaris (MIC value of 3.72 μg/ml). Conclusion: The results of this study showed the significant antibacterial activity of some plants pollen extracts. More studies are needed to further assess the active compounds in the pollen extracts and their cytotoxic effects.